Transhumanism in emerging technoscience as a challenge for the humanities and technology assessment - Coenen, Christopher (Teorija in praksa, 2014)
The shaping of emerging technoscience by transhumanist ideology can be deemed a challenge for both, the interdisciplinary field of technology assessment (TA) and the humanities. The discourses on nanotechnology, "converging technologies" and "human enhancement" respectively are major examples of the influence of transhumanism on areas of new and emerging science and technology. It is argued that TA and the humanities often need to engage more strongly with transhumanism, as an ideology and a sociocultural movement, in order to help make sense of emerging fields of technoscience and their relevance for society.
Keywords: humanism; Humanizem; Nanotechnology; Nanotehnologija; New technologies; Nove tehnologije; Science; Znanost